Branchiopoda (Crustacea: Anostraca and Diplostraca) diversity in Tajik Pamir and plain West and South Tajikistan - Dadykin, Ivan A.; Karimov, Gafur N.; Sinev, Artem Y.; Volkova, Polina A.; Kotov, Alexey A. (Zootaxa, 2024)
Here we attempt to clarify a faunistic composition of branchiopods from southern Tajikistan and the southern part of the Tajik Pamir Plateau (Central Asia) based on samples collected from June 24 to July 6, 2023. In total, 19 species of branchiopods were identified from plain West and South Tajikistan, and 27 species were recorded in Tajik Pamir. Five taxa were newly recorded for the territory of Tajikistan: Chirocephalus cf. bobrinskii (Alcock, 1898), Ceriodaphnia dubia Richard, 1894 s. lat., C. megops Sars, 1862, Ilyocryptus spinifer Herrick, 1882, and Anthalona harti harti Van Damme, Sinev & Dumont, 2011. The previous identifications were corrected for four more taxa. Morphological traits and taxonomic position of several species were discussed in detail, namely two abovementioned anostracan taxa, Eulimnadia behningi Smirnov, 1949 (Spinicaudata), Anthalona harti harti and Coronatella rectangula (Sars, 1861) (Anomopoda). To date, the faunistic list of Tajikistan includes 77 valid branchiopod taxa. Plain Tajikistan is inhabited by both boreal and tropical branchiopod species, what indicates its geographic position on the edge of the Palearctic. Tajik Pamir fauna includes a specific component of alpine species and regional endemics. Complex relief and geographic position of Tajikistan make it prospective for future faunistic, biogeographic and phylogeographic research.